Floodplain Modelling by Using HEC-RAS at Batu Pahat River, Johor - QAZI MUMTAZ, NUR AFEERA; ABUSTAN, MUHAMMAD SALLEH (Recent Trends in Civil Engineering and Built Environment, 2022)
Malaysia is a country that is often hit by monsoonal and flash floods. Heavy seasonal monsoon rains bring extensive long-term floods to many riverine and coastal regions each year. People and property in the floodplain area are at risk of being destroyed when rivers overflow. It is essential to model the flood plain to enhance the necessary steps for future flood prevention. This study aims to create a floodplain modelling using Hydrologic Engineering Centers River Analysis System (HEC-RAS) at Batu Pahat river, Johor. This study applied one-dimensional steady flow analysis to the Batu Pahat River. To conduct the analysis, this study collects the necessary data, such as hydrological data, stream lengths, riverbank stations, and flow data for each river station. To meet the extra volume of water flowing into the river, a total of 4 flow rates were used to identify the increase of water level.  From this study, water overflows into the floodplain from 7 out of 14 stations with a maximum flow rate of 768.50 m3 /s. The results also show one station started to flood with a flow rate of 98.5 m3 /s. Analysis from this study has demonstrated that HEC-RAS can easily identify the results of the affected area. This study can help future reference in flood management, development planning, flood control, and alert the community. It is also essential to show that HEC-RAS is reliable software to use for river analysis and modelling.